Conceptual Understanding of the Peculiarities of Managing Innovation-Driven Development of the State in the Current Conditions - SYTNYK, H.; ZUBCHYK, O.; OREL, M. (Science and Innovation, 2022)
Introduction. The financial, economic, and technological aspects dominate in ensuring innovation-driven development of any state, while the conceptual understanding of the peculiarities of managing this development is often underestimated. Problem Statement. The trajectory of innovation-driven development is turbulent because of the nonlinear nature of management of this development, so the conceptual understanding of the peculiarities of this management is an important factor in terms of effective innovation policy. Purpose. The purpose of this research is to get a conceptual understanding of the peculiarities of national innovation-driven development management in the current conditions of state formation. Materials and Methods. Analytical review of regulations and scholarly theses with the use of content analysis, structural, functional, systemic, comparative, and abstract logical methods. Results. A prerequisite for solving the problems of national innovation-driven development is the introduction of an approach that allows overcoming the institutional weakness of the state, given the presumption of instability and uncertainty of its existence. It has been proposed to consider this development as the introduction of new political and managerial processes, models and technologies, which ensure an acceptable level of national security. It has been shown that political technologies may be used for mind games in choosing the priorities of this development, and its nonlinear dynamics necessitates revising the goals, methods, and technologies in the activities of government entities and ensuring balance between its political and administrative components. Conclusions. The strategic imperative for reducing technological gaps between states is to take into account the turbulence of the trajectory of their innovation-driven development, which is typical for the nonlinear nature of its management, so both the innovation policy and mechanisms for its implementation shall take into consideration the instability and uncertainty of the state being.